Youth Language Dynamics: Javanese Krama in The Globalization Context - Agustuin, Anita Elvy; Abidin, Ali Zainal; Izzah, Maulida Rahmatul; Arnan, Silta Nathan Revi (Universitas Teknokrat Indonesia, 2025)
This research aims to explain the influence of globalization on young people's use of the Javanese krama language, especially for university students. It used a qualitative approach, with open interviews as the primary information collection technique, to learn more about how globalization has impacted young people's usage of Javanese. This research applies descriptive analysis to understanding the impact of globalization on fluency, self-confidence, and the understanding of Javanese krama language in the youth generation. These findings show that from five interviewees, globalization affects the fluency and comprehension of Javanese Krama, and youth speakers needed more confidence to use Javanese Krama, either afraid of mispronunciation or not understanding the word. Globalization has impacted the use of Javanese Krama in the youth generation as an environmental factor; more often, Javanese Ngoko (casual Javanese) or Bahasa Indonesia is used as a means of communication in daily life. This research emphasizes the importance of preserving the use of Javanese Krama in the context of globalization.Keywords: Krama Javanese, Globalization, Youth